Orthopedic Nuclear Medicine - Elgazzar, Abdelhamid H. (Springer International Publishing : Imprint: Springer, 2017)
This book, now in a revised and updated second edition, offers a comprehensive overview of the state of the art in orthopedic nuclear medicine, including the impressive recent advances in the field and the diagnosis of under-recognized conditions on the basis of their imaging patterns. The opening chapters acquaint the reader briefly with anatomic, physiologic, pathologic, and technical concepts crucial to a sound understanding of orthopedic nuclear medicine and its utilization in clinical practice. The imaging diagnosis of skeletal infections, trauma, vascular disorders, metabolic and neoplastic bone diseases, soft tissue calcifications, and joint disorders is then explained in detail. Two entirely new chapters, on bone marrow imaging and hybrid imaging of bone diseases, have been added to this edition. A separate chapter is devoted to the use of radionuclides for the treatment of bone and joint disorders. The book is richly illustrated and amply documents the effectiveness of nuclear medicine in diagnosing bone disease. It will prove invaluable to all with an interest in diagnostic and therapeutic orthopedics, including orthopedists, radiologists, rheumatologists, pediatricians, podiatrists, other clinicians, and all nuclear and molecular imaging professionals.